PENGEMBANGAN LITERASI BUDAYA DAN KEWARGAAN ANAK USIA DINI DI SANGGAR ALLEGRO DESA PODO KEC. KEDUNGWUNI KAB. PEKALONGAN - Siti Mumun Muniroh; Nur Khasanah; Mohammad Irsyad (JURNAL LENTERA ANAK, 2020)
Cultural and civic literacy are important things to master in the 21st century. This is because the diversity of ethnic groups, languages, customs, and customs has begun to be disturbed by people or groups who do not want differences and want to disentangle the cultural wealth possessed by this nation. One effective way to promote cultural and civic literacy is through art galleries. The purpose of this empowerment is to empower students at the Allegro Studio in order to develop cultural and civic literacy so as to increase self-love for the nation. The subjects of this empowerment activity assistance are 20 (twenty) students at the Allegro Studio. The results of this empowerment program are (1) Allegro studio student training has been carried out, (2) The resulting recording and making of video clips of songs created by the Pokja Team and Allegro Studio Team entitled